The morphological affinities of the Middle Pleistocene hominin teeth from Pontnewydd Cave, Wales. (October 2015) - Compton, Tim; Stringer, Chris
ABSTRACT: Seventeen Middle Pleistocene hominin teeth were excavated at Pontnewydd Cave in North Wales between 1980 and 1995 with a probable age of ∼225 ka, associated with handaxe and levallois artefacts. Their Neanderthal characteristics and their affinities with other European Middle Pleistocene teeth and the major sites of Atapuerca‐SH in Spain and Krapina in Croatia are explored. The Pontnewydd teeth are shown to have a marked similarity to those of Atapuerca‐SH, more pronounced than similarities to teeth from other European Middle Pleistocene sites, and to belong in the pre‐Neanderthal stage of Neanderthal evolution. Distinct dental morphological differences between later European Middle Pleistocene specimens, together with those from Atapuerca‐SH, and European Middle Pleistocene Homo heidelbergensis specimens are identified, contradicting the view that both the Pontnewydd and the Atapuerca‐SH fossils belong in that species. Additionally, the similarities in dental morphology between European and non‐European H . heidelbergensis specimens are demonstrated. We argue that when sites are grouped together for comparative purposes this should be done on morphological grounds, and not by apparent date, in view of the possible contemporaneity of European Middle Pleistocene sites that exhibit different degrees of Neanderthal affinities.